P‐2: High‐Performance LTPO TFT‐LCD Using Metal as Hydrogen Barrier Layer. Issue 1 (28th June 2021) - Luo, Chengzhi; Yin, Guoheng; Shu, Zhaowei; Liu, Guanghui; Ai, Fei
Abstract : Low‐Temperature Poly‐Si and Oxide (LTPO) thin‐film transistors (TFTs) have been successfully manufactured and adapted to 6.3 inch liquid crystal display (LCD) panels. To avoid the introducing of hydrogen (H) to oxide TFTs when passivating the Poly‐Si TFTs, the metal barriers are used to prevent the diffusion of hydrogen from the bottom layers. It is shown that those oxide TFTs built with metal barriers exhibit improved intrinsic resistance against hydrogen‐induced degradation. The optimum processes conditions have been used on the 6.3 inch LTPO LCD with ultra‐wide frame rate from 1 to 120 Hz. Further, the specifications of the prototype displays for 409‐ppi LCD with low power consumptions and superior flicker under 1‐Hz frame‐rate driving are reported.